Implementasi Pendidikan Karakter dalam Mata Pelajaran Pendidikan Kewarganegaraan pada Siswa Sekolah Dasar - Irzal Anderson; Riana Sari (Jurnal Gentala Pendidikan Dasar, 2016)
The purpose of this study is to describe the implementation of character education in civic education subjects in class VI SDN 20/1 Jembatan Mas, Pemayung sub-district. This research is descriptive qualitative, namely research that can reveal facts comprehensively about the implementation of character education in civic education subjects in Class VI Students of SD Negeri 20/1 Jembatan Mas, Pemayung District. The subjects of this study were 2 grade VI teachers SDN 20/1 Mas bridge Pemayung sub-district with data collection techniques through interviews, observation, distributing questionnaires and documentation of supporting data. The results of this study show a description of the Implementation of Character Education in Citizenship Education Subjects in Class VI Students of SD Negeri 20 / I Jembatan Mas, Pemayung Subdistrict which has been well implemented through the stages of planning and implementing learning, and solutions to obstacles in the implementation of character education in PKn subjects.